So You Want a Meade LX Telescope! How to Select and Use the LX200 and Other High-End Models - Harris, Lawrence (The Patrick Moore Practical Astronomy Series,, 2010)
The revolutionary computer-controlled Meade LX200 series of telescopes was introduced in 1992 and represented a giant step forward in technology. The series was an instant success, and Meade LX200 telescopes have since sold in huge numbers compared with many other astronomical telescopes! The LX200s are extraordinary telescopes capable of producing amazing results, but managing them can be a chore. So You Want a Meade LX Telescope! includes the essential hardware operations and reviews the best of the many software packages available to aid you in the setting up and use of the telescope. Typical results and various ways to achieve these results are given in detail, so readers can know what to expect from construction to image. Also included are reviews of essential accessories such as CCD cameras and the latest "active optics" units. This book gives readers the benefit of Harris's many years of experience as both a professional astronomer and owner of Meade LX telescopes, including the top end LX400. For anyone owning or considering buying a high-end Meade telescope, this book is the most valuable accessory you can buy!